Imunidade tributária e os deveres instrumentais: instituição e sanções - Deus, José Renato Pereira de (2011)
The thesis for the Master s degree conclusion aims at analyzing tax immunities, especially the unconditional immunity and the introductory vehicles of instrumental duties to taxpayers granted with immunity, giving as example the immunity of paper for printing, regulated by the Normative Instruction no. 976/2009. In order to do so, we delimited our reference system to knowledge and language, since we believe that language is responsible for strengthening not only the world around us, but also the legal reality, where there are no objects outside the language boundaries. Tax immunity was defined as a set of legal rules that establish through a forbidden deontic modality that government and tax agencies come to issue rules levying taxes. We then focused on the range of immunity rule, its relation with rules of instrumental duties, its application, and the distinction between exemption and non-levy. The method used is dogmatic while the technique is analytical hermeneutics, seeking to position the work within the doctrinal line called logicosemantic constructivism